The Influence of Football Player Endorsement on Company Credibility, Ad Credibility, and Brand Credibility at East Hooligan Apparel Store - Thomi Yasri Setiawan; Raden Roro Ratna Rostika (Asian Journal of Social and Humanities, 2023)
This research aims to examine and analyze the effect of celebrity trust with the use of endorsed football players on company credibility, advertising credibility, and brand credibility at the East Hooligan Apparel store. Model and hypothesis testing were clear using a sample of 250 respondents with a population of consumers who were interested in the use of football attributes such as jersey, shirt, jacket, and others. The sampling technique used was purposive sampling. The Structural Equation Modeling (SEM) method was developed to test the research hypothesis which was processed using Partial Least Square (PLS) version 3.0. The data variables used in this case include celebrity trust, company credibility, advertising credibility and brand credibility. These variables form 6 hypotheses. Based on the results of the study, it is known that celebrity trust has a positive effect on advertising credibility, company credibility, and brand credibility. In addition, advertising credibility has a positive effect on company credibility and also brand trust has a positive effect on advertising credibility and company credibility.